Conceptual Frames of Fatherhood in Indonesian Song Lyrics: A Cognitive Linguistic Analysis of “Cinta Sejati Takkan Mati” - Rahmah, Neneng Farida; Muman (Universitas Islam Negeri Palopo, 2025)
Song lyrics represent cultural texts rich in emotional and symbolic meaning. This study employs qualitative content analysis using a frame semantics approach to analyze the lyrics of “Cinta Sejati Takkan Mati” by Agus Subianto (2025b), the original soundtrack of the film Believe (released in 2025), as an object of cognitive linguistic inquiry. The data consist of the complete lyrics of a single song, examined to explore the conceptual representation of the father figure of Indonesian culture. Drawing on frame semantics (Fillmore, 1982) and the principles of embodied cognition (Johnson, 2007), the analysis identifies five primary semantic frames: (1) Father as Eternal Love, (2) Father as Silent Sacrifice, (3) Father as Living Memory, (4) Father as Source of Validation, and (5) Father as Eternal Guardian. The findings reveal that the father is represented not merely as a biological figure, but as a multidimensional emotional and spiritual symbol that shapes the child’s identity through embodied affective experience. The song constructs paternal love as transcendent and immeasurable, reinforcing cultural narratives of the father as a moral and emotional anchor within the family. This study expands the application of cognitive linguistics in popular culture analysis and demonstrates how song lyrics function as cultural media that reflect and shape collective understandings of emotion, family relationships, and spirituality.